Design, Synthesis and Hydrogen Bonding of B3N6‐[4]Triangulene. (20th August 2021) - Zhao, Mengna; Miao, Qian
Abstract: Replacement of the allylic C=C−C unit with a N−B−N unit at each of the three zigzag edges of [4]triangulene gives rise to B3 N6 ‐[4]triangulene, which is envisioned to represent a key structural unit of a new hypothetical boron carbon nitride (BC4 N). A tert ‐butylated B3 N6 ‐[4]triangulene has been successfully synthesized by three‐fold nitrogen‐directed borylation, and the X‐ray crystallographic analysis indicates that its slightly bent triangular polycyclic framework can be viewed as a 1, 3, 5‐triphenylbenzene connected by three 4π‐electron N−B−N units. The HN−B−NH moiety provides a dual hydrogen‐bond donor, which forms H‐bonds with halide or carboxylate anions in solution, and form DD‐AA hydrogen‐bond arrays with 2, 7‐di( tert ‐butyl)‐pyrene‐4, 5, 9, 10‐tetraone in the co‐crystal. Moreover, the blue fluorescence of B3 N6 ‐[4]triangulene in solution is responsive to binding p ‐nitrobenzoate anion through hydrogen bonds. Abstract : B3 N6 ‐[4]triangulene, which is isoelectronic to the trianion of [4]triangulene, represents a key structural unit of a new hypothetical boron carbon nitride. The tert ‐butylated derivative of B3 N6 ‐[4]triangulene is synthesized by threefold nitrogen‐directed borylation. Its fluorescence in solution is responsive to binding p ‐nitrobenzoate anion through H‐bonds, and it forms DD‐AA H‐bond arrays with di( tert ‐butyl)‐pyrenetetraone in the co‐crystal.